China's Belt and Road Initiative the impact on sub-regional Southeast Asia - Ploberger, Christian; Ngampamuan, Soavapa; Song, Tao (Associate professor) (London : Routledge, 2021)
This book evaluates China's relations with sub-regional Southeast Asia through its Belt and Road Initiative (BRI) and the Lancang-Mekong Cooperation framework. The book looks at domestic drivers and regional receptivity of China's Belt and Road Initiative and also delves into the challenges of China's engagement in the Greater Mekong Sub-region. The book examines how China's BRI will contribute to the development of these countries, to regional economic integration and cooperation processes within a political-economic context. It addresses the BRI process within the GMS on three levels: regional, individual recipient countries and the Chinese perspective. The case studies in the book will help to provide insights on China's growing economic influence in sub-regional Southeast Asia and its Belt and Road Initiative. This book will appeal to researchers interested in the BRI, China's relations with Southeast Asia and China's neighbourhood policy and how domestic considerations are influencing China's policy making.
Keywords: Yi dai yi lu (Initiative : China); China -- Foreign economic relations -- Southeast Asia; Southeast Asia -- Foreign economic relations -- China; Southeast Asia -- Economic conditions; POLITICAL SCIENCE / Economic Conditions; POLITICAL SCIENCE / Globalization